Role of the Host Cell's Unfolded Protein Response in Arenavirus Infection - Pasqual, Giulia (American Society for Microbiology (ASM), 2011)
Arenaviruses are enveloped RNA viruses with a nonlytic life cycle that cause acute and persistent infections. Here, we investigated the role of the host cell's unfolded protein response (UPR) in infection of the prototypic arenavirus lymphocytic choriomeningitis virus (LCMV). In mammalian cells, the endoplasmic reticulum (ER) chaperone protein GRP78/BiP functions as the principal sensor for the induction of the UPR and interacts with three mediators: kinase/endonuclease inositol-requiring protein 1 (IRE1), PKR-like ER kinase (PERK), and activating transcription factor 6 (ATF6). Acute infection with LCMV resulted in a selective induction of the ATF6-regulated branch of the UPR, whereas pathways controlled by PERK and IRE1 were neither activated nor blocked. Expression of individual LCMV proteins revealed that the viral glycoprotein precursor (GPC), but not that of other viral proteins, was responsible for the induction of ATF6. Rapid downregulation of the viral GPC during transition from acute to persistent LCMV infection restored basal levels of UPR signaling. To address a possible role of ATF6 signaling in LCMV infection, we used cells deficient in site 2 protease (S2P), a metalloprotease required for the activation of ATF6. Cells deficient in S2P showed significantly lower levels of production of infectious virus during acute but not persistent infection, indicating a requirement for ATF6-mediated signaling for optimal virus multiplication. In summary, acute LCMV infection seems to selectively induce the ATF6-regulated branch of the UPR that is likely beneficial for virus replication and cell viability, but it avoids induction of PERK and IRE1, whose activation may be detrimental for virus and the host cell.